Broadening the foundation for the study of childhood connectedness to nature - Beery, Thomas; Djerf, Henric; Wünsche, Tanya Uhnger; Fridberg, Marie (Frontiers in Environmental Science, 2023)
The spatial aspect of access to nature experience is considered a key factor for studying school-age educare and connectedness to nature. While the standard approach for questions of connectedness to nature is to study at the individual level using methods such as observations, psychometric scaling, and interviews, less common are spatial methods applied to structural or collective aspects of these questions; connectedness to nature study rarely considers the human relationship with nature across sociocultural/structural/institutional levels. Spatial analysis is presented as a step toward a broader consideration of connectedness to nature; careful consideration of connectedness to nature/disconnection must explore the forces beyond the individual shaping access and opportunity. Specifically, the study considers access through proximity to nature from school-age educare sites in the Swedish city of Malmö. Using spatial methodology, proximity to nature was measured at 67 school-aged educare sites. The results provide a complex picture of a range from high to low-quality access to nature for children at the sites. The results help highlight the importance of access via proximity while also opening the door to a mix of other sociocultural/structural/institutional factors to be considered in support of children’s access to nature experience.